Evaluating the feasibility and acceptability of the Informed Health Choices-Cancer programme: A pilot randomised trial protocol - Mengqi Li; Marie Tierney; Claire Beecher; Maura Dowling; Austin G. Duffy; Caitriona Duggan; David Robert Grimes; Avril Kennan; Claire Kilty; Allen Nsangi; Andrew D. Oxman; Derek C. Stewart; et al. (PLoS ONE, 2025)
Background More than one-third of cancer-related health information is unreliable or misleading. With increasing health information seeking, the risks of misinformation exposure are growing. Educational approaches that are delivered clearly and in accessible formats are a promising way to strengthen critical thinking and decision-making skills, thereby helping to reduce the exposure of those impacted by cancer to misleading cancer information. Methods This pilot randomised trial will assess the feasibility and acceptability of conducting a larger definitive trial evaluating the Informed Health Choices-Cancer (IHC-C) programme. The IHC-C is an online evidence-based education programme co-designed by stakeholders, including public and patient partners. It aims to equip people impacted by cancer (i.e., current patients, survivors, caregivers, and loved ones) with the skills and knowledge necessary to think critically about the reliability of health information and claims and make informed health choices. Participants will be randomised to either the IHC-C intervention group or a waitlist control group. The primary outcome of this pilot trial are feasibility (recruitment and retention rates, etc.) and acceptability (participant satisfaction and perceived usefulness, etc.). Demographic and cancer-related data will be collected to characterise the sample and inform recruitment strategies for a future definitive trial. Preliminary measures of critical thinking and decision-making skills will also be gathered to support the selection of key outcomes for the future trial. Discussion This pilot trial will inform the design and conduct of a future definitive randomised trial. Insights gained will inform sample size estimations, refine recruitment strategies, optimise programme delivery, and improve data collection processes, ensuring a robust and scalable approach for the definitive trial.